2015
DOI: 10.15252/embr.201540689
|View full text |Cite
|
Sign up to set email alerts
|

Synaptotagmin‐11 inhibits clathrin‐mediated and bulk endocytosis

Abstract: Precise and efficient endocytosis is essential for vesicle recycling during a sustained neurotransmission. The regulation of endocytosis has been extensively studied, but inhibitors have rarely been found. Here, we show that synaptotagmin-11 (Syt11), a non-Ca 2+binding Syt implicated in schizophrenia and Parkinson's disease, inhibits clathrin-mediated endocytosis (CME) and bulk endocytosis in dorsal root ganglion neurons. The frequency of both types of endocytic event increases in Syt11 knockdown neurons, whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(66 citation statements)
references
References 66 publications
(108 reference statements)
2
61
0
Order By: Relevance
“…In macrophages, Syt11 inhibits IL‐6 and TNF‐α secretion (Arango Duque et al, ), which is mediated by constitutive conventional exocytosis (Murray & Stow, ). Previously, we reported that Syt11 does not affect Ca 2+ ‐regulated evoked exocytosis in dorsal root ganglion and hippocampal neurons (Wang et al, ). Here, we report that Syt11 specifically inhibited the conventional secretion of IL‐6 and TNF‐α without affecting the unconventional secretion of IL‐1β or NO release (Figure ).…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…In macrophages, Syt11 inhibits IL‐6 and TNF‐α secretion (Arango Duque et al, ), which is mediated by constitutive conventional exocytosis (Murray & Stow, ). Previously, we reported that Syt11 does not affect Ca 2+ ‐regulated evoked exocytosis in dorsal root ganglion and hippocampal neurons (Wang et al, ). Here, we report that Syt11 specifically inhibited the conventional secretion of IL‐6 and TNF‐α without affecting the unconventional secretion of IL‐1β or NO release (Figure ).…”
Section: Discussionmentioning
confidence: 88%
“…shSyt11‐resistant Syt11 expression construct (CMV‐myc‐Syt11‐IRES2‐BFP) for Rescue experiments were generated by introducing silent mutations as follows: ATG GCG GAA ATT ACC AAT ATA CG. A random sequence that was predicted to target no genes in human, rat, and mouse cells was chosen as a negative control (Wang et al, ). For Syt11 silencing or rescue experiments, microglia were processed 7 days after lentivirus infection.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…EM imaging. EM of adrenal slices was performed according to previous descriptions with minor modifications (de Wit et al, 2009a;Wang et al, 2016). The adrenal glands were extracted from adult WT and dyn1-KO mice and then the adrenal cortex was removed and the medulla was cut into 1-2 mm 3 pieces.…”
Section: Methodsmentioning
confidence: 99%
“…26,37 Previously, we discovered that Syt11 inhibits clathrin-mediated and bulk endocytosis in neurons as well as cytokine secretion and phagocytosis in microglia. 38,39 Here, we report that Syt11 also inhibited caveolae-mediated endocytosis, most likely via direct interactions with cavin1 and EHD2, but not Cav1. Surprisingly, we discovered that Syt11 positively regulated the mechanosensitive and mechanoprotective functions of caveolae and astrocyte swelling.…”
Section: Introductionmentioning
confidence: 68%